Orthogonal array technique for optimizing the sintering parameter of the metal injection molding (MIM) compact: best flexure strength - Jamaludin, Khairur Rijal; Muhamad, Norhamidi; Ab. Rahman, Mohd. Nizam; Ahmad, Sufizar; Irwan Ibrahim, Mohd. Halim; Mohamad Nor, Nor Hafiez (2009)
Sintering is a key step in the metal injection moulding (MIM) process, which affects the mechanical properties of the sintered part. The mechanical property of the sintered compact is resulted from tremendous sintered part densification. The paper presents an optimisation of the sintering parameter for the best flexure strength of the fine SS316L water atomised powder compact. The L9 (34) orthogonal array is used in the study and four replication of the flexure strength has been recorded at each experiment trial. The analysis of variance (ANOVA) shows the sintering variables are highly significant to the flexure strength, a = 0.005. The study demonstrates that the cooling rate is the most influential variable that contributes to the best flexure strength, followed by heating rate, dwell time and sintering temperature